33 'A post code lottery': experiences of healthcare professionals providing palliative care out-of-hours across the UK. (30th January 2023) - Firth, Alice M; Goodrich, Joanna; Gaczkowska, Inez; Harding, Richard; Murtagh, Fliss EM; Evans, Catherine
Abstract : Introduction: Patients and their families receiving palliative care in the community rely on 'out-of-hours' services over 70% of the time. Although distressing symptoms, or new problems may arise at any time., out-of-hours service availability and provision across the UK varies widely. Aims: To understand current service provision and availability of out-of-hours care across the UK for patients and families receiving specialist palliative care. Methods: Semi-structured qualitative interviews with healthcare professionals across the UK providing out-of-hours community palliative care. Transcripts were analysed thematically to explore and identify models and components of out-of-hours care. Results: 28 interviews were conducted with 39 participants, including: GPs, community nursing teams, and palliative care medical consultants and specialist nurses. Four overarching models of out-of-hours care were identified, based on levels of integration and balance between generalist and specialist care out-of-hours, and type of care available (hands-on care/advisory care). These showed large service variation from a uni-disciplinary single service by out-of-hours GPs to multidisciplinary via a dedicated 24/7 telephone line staffed by specialist palliative care nurses supported by integrated community and specialist palliative care services, providing hands-on clinical and advisory care. Conclusions: The study identified community out-of-hours palliative care as highly varied from sole reliance on GPs to provision by integrated multidisciplinary specialist and generalist teams. Sampling across providers, disciplines, and geography, identified four overarching models of out-of-hours care and key components, including level of integration between services and variability of care provision. Impact: The study identifies the inequity and 'post-code lottery' for patients and families requiring palliative care out-of-hours. The findings inform the strategic planning and provision of palliative care services by commissioners and service providers